Pemikiran Ekonomi Islam Ibnu Khaldun dalam Kitab Muqaddimah dan Relevansinya Terhadap Perekonomian Indonesia - Fauziyah Latiefa Salsabila; Abd. Chair (Muttaqien, 2024)
The classical and medieval Islamic periods had historians who tried or made efforts to record every important event, one of them was Ibn Khaldun. Ibn Khaldun Ibn Khaldun in his book Muqaddimah describes the problems of social life, one of which is the problem of Islamic economics. This article aims to find out the biography of Ibn Khaldun, the historiography used by Ibn Khaldun in writing history, and Ibn Khaldun’s thoughts regarding Islamic economic theory and its relevance against Indonesian economy. These theories include, trade and markets, taxes, production and distribution, market mechanisms and monopolies, and import-export theory. This study uses library research with a qualitative approach, by using the Book of Muqaddimah as the primary source. Meanwhile, secondary sources are taken from other books and journals. Ibn Khaldun argues that economic theories must coincide with Islamic values. With that, the Islamic economic theory initiated by Ibn Khaldun presents novelty by looking at its relevance against Indonesian economy.